(3TQa GdehVhY HHjGf GdehVhYs - (3Ndjd Hf eMeO GdeZQHj, CHh GdeQTO,J (B1177 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd GdYHO GdabjQ Ndjd GdeGdci bO SCdfi CYR GdGMHGH s
(3BNQgG (B:s
(3hGdEfSGf CNU ef GdMjhGf eWbG hGdNGQL GdCYe ef hLg GdCNU s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B322 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B127s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCgdjI HHGQjS s
Keywords: (3GdadSaI hGdefWbs